A comparison of selected anthropometric, metabolic and hormonal variables in lightweight and open class rowers - Jürimäe, J.; Jürimäe, T. (2001)
The aims of this study were to compare: 1) the possible differences in anthropometric, metabolic and basal levels of hormonal variables between lightweight and open class rowers; and 2) how specific anthropometric, metabolic and resting hormonal characteristics are related to the performance parameters in lightweight and open class rowers. Nine lightweight (20.44± 4.69 yrs; 182.33± 2.96 cm; 71.39± 1.99 kg; %body fat: 10.04± 1.31%) and 11 open class (21.55± 2.98 yrs; 191.09± 4.69 cm; 87.11± 6.16 kg; %body fat: 10.45± 2.58%) national level rowers were subjected to two exercise sessions on a rowing ergometer (Concept II, Morrisville, USA). An incremental exercise test to determine the anaerobic threshold (AT4), maximal oxygen consumption (VO2max) and maximal aerobic power (Pamax), and a 2000 metre "all-out" test were performed. In addition, sum of six skinfolds, muscle mass, skeletal mass and cross-sectional area of thigh from the anthropometric parameters, and cortisol and testosterone levels were determined. The anthropometric and metabolic characteristics of lightweight rowers were significantly lower in comparison with open class rowers. No significant differences were observed in the measures of leannes and relative VO2max between studied groups. No significant differences existed in the basal hormone levels between lightweight and open class rowers. The hormone values were significantly related to the performance parameters in open class rowers. In summary, the results of the present study suggest that performance values are significantly related to the specific anthropometric characteristics in lightweight and open class rowers. In addition, a certain level of performance has to be reached before a significant relationship could be observed between basal levels of hormones and performance parameters.